ANALYSIS OF THE ROLE OF SAVING AND LOAN CREDIT IN PNS RETIREMENTS IN THE NASARI SAVING AND LOAN COOPERATIVE (KSP) KOTA LHOKSEUMAWE - Putri Rahmayani; Hastanti Listya Ningtiyas; Sultan Haris Al-Muridhillah; Chairul Rizal; Subhan Subhan (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This study aims to determine the growth of pension credit at the Nasari Savings and Loans Cooperative, Lhokseumawe City. The methodology used in the research process is descriptive qualitative, namely knowing the growth of pension credit each year at the Nasari Savings and Loans Cooperative, Lhokseumawe City, using existing data. The analysis used in this research is trend analysis. The results showed that the growth of pension credit in the Nasari Savings and Loans Cooperative fluctuated and tended to decrease with the average credit growth. The author gives advice to the Nasari Savings and Loans Cooperative in Lhokseumawe City in order to reduce interest rates on pension credit loans, so that they can compete with other cooperatives and increase credit growth every year.